Analisis komparatif unsur kinetic typography dalam title sequence film - Luthfiasari, Annisa; Fadillah, Citra (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2023)
Typography, usually closely related to printed media, has now been explored in digital media. These changes make typography, which is usually static, more dynamic. One example of digital typography is kinetic typography. Typography's position as a medium of visual and textual communication becomes more interesting because the element of motion in kinetic typography adds another meaning value. This study examines how typography reveals meaning in time-based media formats. In this study, three movie title sequences with different genres will be analyzed: Monsters Inc., Se7en, and Mission: Impossible — Ghost Protocol. The film was chosen because it has a dominant kinetic typography structure and has a good reputation in terms of visuals. The method of analysis is carried out by comparing the structure of the three title sequences based on the kinetic typography theory by Bellantoni and Woolman. Furthermore, an analysis of the semantic value of each title sequence was also carried out. This research is aimed to figure out the elements used in the visual creation of a title sequence and how these elements can construct meaning. From the analysis process it is known that each genre of the title sequence has different element variations which of course have their own meaning. The results of this study are expected to provide recommendations for the title sequence design method based on the genre like comedy animation, thriller, and action.